SEQUENTIAL COCONUT TODDY (SAP) AND NUT PRODUCTION - J.N. MARAVILLA; S.S. MAGAT (International Coconut Community Journal, 1993)
Production schemes, namely sequential, production of coconut sap/toddy and nuts in same spathe/spadix (SCTNP); nut production only (NP) and toddy production only (CTWS) were tested at PCA Davao Research Center, using Laguna Tall for a period of three years. Palms under the CTWS and the SCTNP had more coconut sap yield over the periodic tapping and nut production (3 or 6 month’s duration) in three years of tapping operation. Annual toddy yield in the SCTNP did not differ significantly with the CTWS during the first and third years of tapping. Generally nut yield of palms with SCTNP was about 50% lower than control palms (NP). As compared to palms under NP, copra yield per palm with SCTNP was likewise around 50% lower. Leaf nutrient concentrations of N, P, K. Ca. Mg, Na, Cl, S and B were not significantly affected by toddy‑lapping under the four production schemes. Results clearly showed that the sequential coconut toddy and nut production (SCTNP) is strongly feasible and economically viable to supply both toddy and nuts as farm products by small scale coconut farmers. Compared to the traditional practice of producing nut alone (P 7,500.00 per ha average annual income), SCTNP provides an average net income of P 71,000.00 per ha (P 520.00 per tree), annually.